From the ‘rationalist consensus’ to ‘exclusive incrementalism’: the ‘new’ German policy style - Zohlnhöfer, Reimut; Tosun, Jale (The Routledge handbook of policy styles, 2021)
In this chapter, we argue that the overarching policy style in Germany can be characterised as ‘exclusive incrementalism’. The main characteristic of this policy style is that German policymakers adopt only incremental changes to existing policies unless there is explicit demand for or need of large-scale changes. The reforms are reactions to exogenous events or public opinion rather than attempts to anticipate societal problems, and the policymaking is limited to partisan actors. Our characterisation stands in contrast to the chapter on the German policy style in the original volume, which described the German policy style as a ‘rationalist consensus’. Since the publication of the original volume in 1982, the country’s political system has undergone fundamental changes that include, most prominently, the reunification in 1990 and changes to the party landscape in response to this and other events.